Contraception and Reproductive Planning for Women With Cardiovascular Disease: JACC Focus Seminar 5/5 - Lindley, Kathryn J; Bairey Merz, C Noel; Davis, Melinda B; Madden, Tessa; Park, Ki; Bello, Natalie A (Journal of the American College of Cardiology, 2021)
The majority of reproductive-age women with cardiovascular disease are sexually active. Early and accurate counseling by the cardiovascular team regarding disease-specific contraceptive safety and effectiveness is imperative to preventing unplanned pregnancies in this high-risk group of patients. This document, the final of a 5-part series, provides evidence-based recommendations regarding contraceptive options for women with, or at high risk for, cardiovascular disease as well as recommendations regarding pregnancy termination for women at excessive cardiovascular mortality risk due to pregnancy.